2007
DOI: 10.1186/1472-6963-7-96
|View full text |Cite
|
Sign up to set email alerts
|

Practice size, caseload, deprivation and quality of care of patients with coronary heart disease, hypertension and stroke in primary care: national cross-sectional study

Abstract: BackgroundReports of higher quality care by higher-volume secondary care providers have fuelled a shift of services from smaller provider units to larger hospitals and units. In the United Kingdom, most patients are managed in primary care. Hence if larger practices provide better quality of care; this would have important implications for the future organization of primary care services. We examined the association between quality of primary care for cardiovascular disease achieved by general practices in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 13 publications
2
63
1
Order By: Relevance
“…[22][23][24][25] This is not to deny that deprived populations may face particular disadvantages in gaining access to high quality primary care. Several studies suggest that general practices located in areas of socioeconomic deprivation provide a lower quality of care as judged by QOF scores [26][27][28][29][30] (although it should be acknowledged that other studies find little evidence of socioeconomic inequality 31,32 ). There may also be plausible reasons why, relative to underlying morbidity, deprived groups need greater access to primary care.…”
Section: Original Papers Discussion Papermentioning
confidence: 99%
“…[22][23][24][25] This is not to deny that deprived populations may face particular disadvantages in gaining access to high quality primary care. Several studies suggest that general practices located in areas of socioeconomic deprivation provide a lower quality of care as judged by QOF scores [26][27][28][29][30] (although it should be acknowledged that other studies find little evidence of socioeconomic inequality 31,32 ). There may also be plausible reasons why, relative to underlying morbidity, deprived groups need greater access to primary care.…”
Section: Original Papers Discussion Papermentioning
confidence: 99%
“…23 Also, larger practices may be more likely to incorporate guidelines for the diagnosis and treatment of ADHD, as solo practices may have poorer access to mental health services, limited insurance coverage, and other potential system barriers to the delivery of ADHD care. 29 The association of larger practices with better diabetes management also suggests that there may be positive effects of having a multidisciplinary team, 15,16 that shared care with nurses allowed for certain processes to be effectively performed by nurses, 32 or that larger practices simply have better information technologies to facilitate execution of clinical processes. 10 The mixed results regarding the effects of larger practice sizes on preventive services could be due to methodological limitations, different settings, and varying independent variables and process measures across the studies.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…6 Several studies have compared quality of care in deprived and affluent areas after the introduction of QOF. [7][8][9] These studies have generally found marginally lower achievement of quality indicators in deprived areas, with evidence of near attenuation of these differences in the second and third year of the contract. 10,11 However, the data used for these studies are derived from the financial administration system for QOF which has a number of limitations.…”
Section: Introductionmentioning
confidence: 99%